2018
DOI: 10.3174/ajnr.a5900
|View full text |Cite
|
Sign up to set email alerts
|

Y-Stent-Assisted Coiling of Wide-Neck Bifurcation Intracranial Aneurysms: A Meta-Analysis

Abstract: BACKGROUND: Y-stent-assisted coiling for wide-neck intracranial aneurysms required further investigation. PURPOSE:Our aim was to analyze outcomes after Y-stent placement in wide-neck aneurysms. DATA SOURCES:We performed a systematic search of 3 data bases for studies published from 2000 to 2018. STUDY SELECTION:According to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, we included studies reporting Y-stent-assisted coiling of wide-neck aneurysms.DATA ANALYSIS: Random-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 39 publications
2
66
0
Order By: Relevance
“…However, it is already suggested that the smaller cell size could potentially permit the expansion of a second stent at the intersection point in cases where Y or X-stenting techniques are considered. 26 In addition, we consider this new stent system as a perfect candidate for some alternative stenting techniques such as the 'Flow-T' setting or modified deployment manoeuvres such as the 'railroad switch'. 27,28 On the contrary, there is a certain concern regarding the new LVIS EVO stent observed in our series.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is already suggested that the smaller cell size could potentially permit the expansion of a second stent at the intersection point in cases where Y or X-stenting techniques are considered. 26 In addition, we consider this new stent system as a perfect candidate for some alternative stenting techniques such as the 'Flow-T' setting or modified deployment manoeuvres such as the 'railroad switch'. 27,28 On the contrary, there is a certain concern regarding the new LVIS EVO stent observed in our series.…”
Section: Discussionmentioning
confidence: 99%
“…A recent metaanalysis that investigated the angiographic outcomes of Y-stentassisted coiling procedures reported an immediate occlusion rate of 82.2%. 25 In a recent study, Ciccio et al 16 observed a relatively lower immediate complete aneurysms occlusion rate of 60% following double stent-assisted coiling with the Neuroform Atlas stent. However, 87.5% of partially coiled aneurysms showed progressive to thrombosis in their case series.…”
Section: Figure 2 Procedural and Follow-up Angiography Images Of A 5mentioning
confidence: 96%
“…Two metaanalyses that investigated the outcomes of aneurysms treated with the Y-stent-assisted coiling procedure found that the procedurerelated complication rate was between 8.9% and 12%. 25,26 The open-cell stents were preferred in the first descriptive cases of Y-stenting. The authors reasoned that the open-cell design of the first deployed stent could permit better expansion of the second stent, which was deployed at the interstices of the first stent.…”
Section: Figure 2 Procedural and Follow-up Angiography Images Of A 5mentioning
confidence: 99%
See 1 more Smart Citation
“…However, we have not observed any periprocedural or delayed complications in this subset of patients. A recent meta-analysis by Cagnazzo et al proved that the Y-stenting assisted coiling is an effective treatment for wide-necked intracranial aneurysms with a relatively low rate of treatment related complications [ 18 ]. Table 4 shows aneurysm occlusion rate stratified by number of implanted stents.…”
Section: Discussionmentioning
confidence: 99%